Determining the optimal cholecalciferol dosing regimen in children with CKD: a randomized controlled trial. Issue 2 (24th December 2020) - Iyengar, Arpana; Kamath, Nivedita; Reddy, Hamsa V; Sharma, Jyoti; Singhal, Jyoti; Uthup, Susan; Ekambaram, Sudha; Selvam, Sumithra; Rahn, Anja; Fischer, Dagmar-C; Wan, Mandy; Shroff, Rukshana
Abstract: Background: The optimal treatment regimen for correcting 25-hydroxyvitamin D (25OHD) deficiency in children with chronic kidney disease (CKD) is not known. We compared cholecalciferol dosing regimens for achieving and maintaining 25OHD concentrations ≥30 ng/mL in children with CKD stages 2–4. Methods: An open-label, multicentre randomized controlled trial randomized children with 25OHD concentrations <30 ng/mL in 1:1:1 to oral cholecalciferol 3000 IU daily, 25 000 IU weekly or 100 000 IU monthly for 3 months (maximum three intensive courses). In those with 25OHD ≥30 ng/mL, 1000 IU cholecalciferol daily (maintenance course) was given for up to 9 months. Primary outcome was achieving 25OHD ≥30 ng/mL at the end of intensive phase treatment. Results: Ninety children were randomized to daily ( n  = 30), weekly ( n  = 29) or monthly ( n  = 31) treatment groups. At the end of intensive phase, 70/90 (77.8%) achieved 25OHD ≥30 ng/mL; 25OHD concentrations were comparable between groups (median 44.3, 39.4 and 39.3 ng/mL for daily, weekly and monthly groups, respectively; P = 0.24) with no difference between groups for time to achieve 25OHD ≥30 ng/mL (P = 0.28). There was no change in calcium, phosphorus and parathyroid hormone, but fibroblast growth factor 23 (P = 0.002) and klotho (P = 0.001) concentrations significantly increased and were comparable in all treatment groups. Irrespective of dosing regimen, children with glomerular disease had 25OHD concentrations lower than non-glomerular disease (25.8 versus 41.8 ng/mL; P = 0.007). One child had a 25OHD concentration of 134 ng/mL, and 5.5% had hypercalcemia without symptoms of toxicity. Conclusion: Intensive treatment with oral cholecalciferol as daily, weekly or monthly regimens achieved similar 25OHD concentrations between treatment groups, without toxicity. Children with glomerular disease required higher doses of cholecalciferol compared with those with non-glomerular disease.